Harnessing video reaction-based tasks to foster speaking fluency and critical thinking in English: A mixed-method study - Fachriyah, Eva; Nehe, Berita Mambarasi; Hasanah, Arifatul (UPT Bahasa Universitas Tanjungpura, 2025)
In digital era, English language instruction in university, particularly for Communication Studies students, demands innovative pedagogical strategies that go beyond promoting fluency to also foster critical thinking and media literacy. This study explores the implementation of video reaction-based tasks as a digital learning approach to enhance speaking fluency and critical thinking among second-semester Communication Studies students in the English for Communication course at a university in Banten Province, Indonesia. Drawing on Communicative Language Teaching (CLT), Multimodal Learning Theory, and Self-Determination Theory, the method utilizes students’ familiarity with digital media to create authentic, engaging, and reflective speaking opportunities. Using a mixed-method sequential explanatory design, this study collected quantitative data through pre- and post-tests, and qualitative insights from student interviews, classroom observations, and perception surveys. The results showed a statistically significant increase in speaking fluency (mean gain = 12.8, p < 0.05) and critical thinking (mean gain = 14.2, p < 0.05), especially in organizing arguments, using logical reasoning, and articulating personal opinions. Qualitative findings echoed this improvement, revealing enhanced student confidence, motivation, and cognitive engagement with video-based content. Although students faced some technical and emotional challenges, such as editing difficulties and anxiety speaking on camera, they valued the opportunity to plan, reflect, and express ideas in English through multimodal formats. With sufficient scaffolding, technical support, and peer feedback, video reaction tasks present a promising strategy for developing 21st-century skills, including media literacy, critical analysis, and interpersonal communication. This study offers both theoretical and practical insights into digital pedagogy for Communication students.